2012
DOI: 10.1111/j.1469-8137.2012.04166.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative oxidase modulates leaf mitochondrial concentrations of superoxide and nitric oxide

Abstract: Summary• The nonenergy-conserving alternative oxidase (AOX) has been hypothesized to modulate the amount of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in plant mitochondria but there is sparse direct in planta evidence to support this.• Laser scanning fluorescent confocal microscopy and biochemical methods were used to directly estimate in planta leaf concentrations of superoxide (O À 2 ), nitric oxide (NO), peroxynitrite (ONOO ) ) and hydrogen peroxide (H 2 O 2 ) in wildtype (Wt) tobacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
132
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(145 citation statements)
references
References 45 publications
(54 reference statements)
12
132
0
1
Order By: Relevance
“…The development of a monoclonal antibody that recognized all AOX proteins studied to date (Elthon et al, 1989;Finnegan et al, 1999) facilitated the cloning of the gene, which allowed genetic approaches to be used to study AOX (Rhoads and McIntosh, 1991). Studies in tobacco (Nicotiana tabacum) with reduced or increased amounts of AOX (Vanlerberghe et al, 1994) showed that AOX suppresses the production of reactive oxygen species (ROS) in mitochondria (Maxwell et al, 1999;Cvetkovska and Vanlerberghe, 2012a, 2012b, 2013. Investigations with a variety of abiotic or biotic challenges revealed that AOX acts as a survival protein (Vanlerberghe et al, 2009), in that it allows plants to survive and grow better compared with plants that have reduced amounts of AOX.…”
mentioning
confidence: 99%
“…The development of a monoclonal antibody that recognized all AOX proteins studied to date (Elthon et al, 1989;Finnegan et al, 1999) facilitated the cloning of the gene, which allowed genetic approaches to be used to study AOX (Rhoads and McIntosh, 1991). Studies in tobacco (Nicotiana tabacum) with reduced or increased amounts of AOX (Vanlerberghe et al, 1994) showed that AOX suppresses the production of reactive oxygen species (ROS) in mitochondria (Maxwell et al, 1999;Cvetkovska and Vanlerberghe, 2012a, 2012b, 2013. Investigations with a variety of abiotic or biotic challenges revealed that AOX acts as a survival protein (Vanlerberghe et al, 2009), in that it allows plants to survive and grow better compared with plants that have reduced amounts of AOX.…”
mentioning
confidence: 99%
“…Five SOD activities could be visualized, which, based upon their inhibitor sensitivities (see "Materials and Methods"; Cvetkovska and Vanlerberghe, 2012), included one manganese SOD (MnSOD), two iron SODs (FeSODs), and two copper zinc SODs (CuZnSODs). For each of the FeSODs and CuZnSODs, there was one major band of activity (which we termed FeSOD1 and CuZnSOD1) and one minor band of activity (termed FeSOD2 and CuZnSOD2).…”
Section: Resultsmentioning
confidence: 99%
“…In-gel SOD activity assays were done as previously described (Cvetkovska and Vanlerberghe, 2012). Protein carbonyl content was estimated by immunoblotting using the OxyBlot protein oxidation detection kit, following the manufacturer's instructions (EMD Millipore).…”
Section: Other Methodsmentioning
confidence: 99%
“…6,9 On the other hand plant hormone salicylic acid concentration also shows dramatic effect toward AOX expression as low concentration induces AOX whereas higher concentration do not. 10,11 Biochemical control of AOX activity Expression of the AOX genes and protein formation do not determine the activity of the enzyme. AOX are inner mitochondrial membrane protein existing as a homodimer, regulated by 2 step biochemical regulation.…”
Section: Genetic Control Of Aox Respirationmentioning
confidence: 99%